Bidimensional sustainability analysis of lignocellulosic ethanol production processes. Method and case study. (1st August 2014) - Sanchez, Arturo; Magaña, Gabriela; Gomez, Diego; Solís, Mario; Banares‐Alcantara, Rene
Abstract A method is proposed to analyze the environmental and economic sustainability of biorefineries producing lignocellulosic ethanol. The bidimensional method builds on the conceptual design of the production facility (mathematical models of mass and energy balances of each process stage, equipment sizing, and capital costing models) thus enabling the analysis of prospective technologies. The conceptual design articulates the relations among process stages as impact generators (IIG), stakeholders (and their concerns) as impact receivers (EIR), and indicators to measure the environmental and economic impacts of the process facility. Indicators are formulated as functions of process variables and parameters. Overall impacts for each domain are calculated by weighting the indicators using appropriate dimensional functions and scaling factors. Using the proposed method, the conceptual design of a standard biochemical biorefinery provides the basis for building a sustainability framework comprising 15 indicators. While some of the obtained indicators are ubiquitous in the literature, other less common yet important are identified. A case study illustrates the use of the sustainability framework. A single‐product biorefinery is compared against a multi‐product scheme, showing that single‐product schemes may prove, under certain conditions, more sustainable than their multi‐product counterparts. The sustainability framework provides the rationale to clearly identify the causality from IIG to metric values. This information may be used to support the decisions regarding possible improvements of IIG or modifications of weighting parameters in the dimensional functions in order improve the sustainability of the processes under consideration. © 2014 Society of Chemical Industry and John Wiley & Sons, Ltd